Kemampuan Literasi Numerasi Matematika melalui Penerapan Model Pembelajaran Problem Based Learning (PBL) - Irfawandi Samad; Nur, Muhammad Awal (Universitas Cokroaminoto Palopo, 2024)
The low numeracy literacy skills of students are due to the fact that the mathematics learning process has not yet produced the habit in students of reading with reflection and applying thinking and skills in understanding important information in solving problems. The aim of this research is to determine the increase in students' numeracy literacy skills through the application of problem based learning (PBL). This research is classroom action research that describes students' numeracy literacy abilities. The subjects of this research were class VIII students at SMP 1 Mamasa with a total of 15 students. The research results showed that the average numeracy literacy score in cycle I was 64.13 or in the medium category with 20% completeness. The average value of numeracy literacy in cycle II increased to 100 or was in the high category with 100% completeness. The increase in students' numeracy literacy skills was 35.87, which means that the problem based learning (PBL) learning model can improve the numeracy literacy skills of junior high school students